ANALISIS PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN EFEK MODERASI MANAJEMEN LABA (Studi Empiris Perusahaan Non Keuangan yang Terdaftar di BEI Tahun 2018-2020) - Kevin Fatahillah Akbar; Totok Dewayanto (Diponegoro Journal of Accounting, 2022)
This study aims to examine the effect of corporate social responsibility (CSR) on the company's financial performance with the moderating effect of earnings management. The independent variables in this study are environmental-oriented CSR and socially-oriented CSR. While the company's financial performance is the dependent variable using Tobin's Q proxy and earnings management moderating variable.The characteristics of environmental and socially oriented CSR are considered to have a positive influence on the level of company financial performance according to the hypothesis based on legitimacy theory and stakeholder theory. The population in this study are non-financial companies listed on the Indonesia Stock Exchange (IDX) in the period 2018-2020. The sampling method used in this study is a purposive sampling method with predetermined criteria so as to produce 138 samples of non-financial companies to be studied. The data used is secondary data in the form of financial reports and company annual reports obtained through the website www.idx.co.id and financial information from the Bloomberg terminal. This research uses multiple linear regression analysis, classical assumption test, and moderate regression test.The results of the statistical test in this study indicate that the environmental- oriented CSR performance has a significant positive effect on financial performance. Likewise, socially oriented CSR has a significant positive effect on the company's financial performance. Meanwhile, the moderating effect of earnings management has a significant negative impact on environmental and socially oriented CSR on the company's financial performance.